Modified Simplex - Spectrophotometric Determination of Clonazepam via Charge-Transfer Complexation - Zankanah, Faeza Hazim; Dikran, Sarmad Bahjat (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
A simple, sensitive, accurate, and precise spectrophotometric method for the determination of clonazepam (CLNZ) was developed. The method is based on charge transfer reaction between CLNZ and p-Bromanil (p-Br) to form a colored complex. The optimum conditions of complex formation were investigated by (1). Unvariable method, for the optimization of reagent concentration, base concentration, temperature, and time. (2). Multivariable simplex method including the effect of three experimental factors via; reagent concentration, concentration of NaOH and time. The linearity range of CLNZ was (1-30) Î¼g.mL-1 at 378 nm under condition established via simplex method with molar absorptivity (1.9069x104) L.mol-1.cm-1, Sandell’s sensitivity index (0.0165) Î¼g.cm-2, detection limit of 0.2957Î¼g.mL-1, quantification limit 0.9858Âµg.mL-1 and association constant of the formed complex (2333.3). The proposed method has been successfully applied for the determination of CLNZ in pure form and pharmaceutical preparations